2010
DOI: 10.1016/j.jfms.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Survey of infectious and parasitic diseases in stray cats at the Lisbon Metropolitan Area, Portugal

Abstract: A survey of infectious and parasitic diseases of stray cats was carried out using biological samples collected from animals captured during a catch-neuter-release programme in four counties of the Lisbon Metropolitan Area. The main objective was to investigate the potential threat of stray cats for animal and public health. Samples of blood, stool, hair and auricular swabs were collected from 231 cats in 27 colonies. Anti-Toxoplasma gondii antibodies were detected in 47/194 samples (24.2%); anti-Leishmania inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
58
3
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 27 publications
(24 reference statements)
12
58
3
6
Order By: Relevance
“…The overall prevalence of 77.1% of helminthes in this study was higher than that reported in other studies involving stray cats in Spain (Miró et al. 2004;Torres et al 2006), Portugal (23.1%) (Duarte et al 2010), Germany (33.6%) (Becker et al 2012) and the UK (34.8%) (Nichol et al 1981b). However, our data are in accordance with those reported by Millán and Casanova (2009) in Majorca Island (Spain) -another popular Spanish tourist destination in Europe-where all the 58 feral cats were parasitized by at least one specie of helminth.…”
Section: Discussioncontrasting
confidence: 67%
“…The overall prevalence of 77.1% of helminthes in this study was higher than that reported in other studies involving stray cats in Spain (Miró et al. 2004;Torres et al 2006), Portugal (23.1%) (Duarte et al 2010), Germany (33.6%) (Becker et al 2012) and the UK (34.8%) (Nichol et al 1981b). However, our data are in accordance with those reported by Millán and Casanova (2009) in Majorca Island (Spain) -another popular Spanish tourist destination in Europe-where all the 58 feral cats were parasitized by at least one specie of helminth.…”
Section: Discussioncontrasting
confidence: 67%
“…Other authors who have found low prevalence addition to the low titers in seroepidemiological studies have questioned the importance of cats as reservoirs of the disease, which reinforces the need for more studies on this subject (MARTÍN-SÁNCHEZ et al, 2007;DUARTE et al, 2010). Kirkpatrick et al (1984) demonstrated that intradermal inoculation of the promastigotes form of L. infantum in six cats leads to a significant rise in antibody titers only 16 weeks after the infection, when no parasite was found in the blood, bone marrow, spleen, or liver.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors likes influence on the parasitic burden in stray cats; geographical region, season of the year, administration of antiparasitic treatment and factors related to population parameters (age, sex, breed) (Mircean et al 2010). Previous studies have usually recorded a high prevalence of parasites in stray and feral cats (Adams et al 2008;Becker et al 2012;Calvete et al 1998;Canto et al 2013;Capari et al 2013;Coman 1972;Duarte et al 2010;Engbaek et al 1984;Jittapalapong et al 2007;Khalafalla 2011;Krecek et al 2010;Labarthe et al 2004;Lefkaditis et al 2014;Millan and Casanova 2009;Ramos et al 2013;Riggio et al 2013;Stoichev et al 1982). In Iran, little is known about the prevalence of gastrointestinal parasites in stray cats.…”
Section: Introductionmentioning
confidence: 99%